Ham, the astrochimp - Hilliard, Richard (Honesdale, Pa. : Boyds Mills Press, 2007)
Describes the role played by the chimpanzee, Ham, in developing manned space flight in the U.S.
Keywords: Ham (Chimpanzee) -- Biography -- Juvenile literature; Manned space flight -- Research -- United States -- Juvenile literature; Chimpanzees -- United States -- Biography -- Juvenile literature; Chimpanzees as laboratory animals -- Juvenile literature; Ham (Chimpanzee); Manned space flight; Chimpanzees